Photoelectric Measurement and Sensing: New Technology and Applications - Feng, Qibo; Li, Jiakun; He, Qixin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on recent developments in laser measurement technologies and innovative applications. Laser-based measurement and sensing technologies have attracted growing attention due to their advantages of high sensitivity and fast responses. Their applications include industrial production, substance analysis, environmental monitoring, and more. In recent years, with the development of laser source and measurement approaches, many new technologies or applications of laser measurement and sensing have appeared. The topics of this reprint include laser measurement and sensing, micro- and nano-photoelectric measurement, the simultaneous measurement of multiple parameters, structured light measurement, and so on.